2022
DOI: 10.3390/diagnostics12040793
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling Pattern of Spinal Canal after Full Endoscopic Uniportal Lumbar Endoscopic Unilateral Laminotomy for Bilateral Decompression: One Year Repetitive MRI and Clinical Follow-Up Evaluation

Abstract: Objective: There is limited literature on repetitive postoperative MRI and clinical evaluation after Uniportal Lumbar Endoscopic Unilateral Laminotomy for Bilateral Decompression. Methods: Clinical visual analog scale, Oswestry Disability Index, McNab’s criteria evaluation and MRI evaluation of the axial cut spinal canal area of the upper end plate, mid disc and lower end plate were performed for patients who underwent single-level Uniportal Lumbar Endoscopic Unilateral Laminotomy for Bilateral Decompression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…One MR radiological study by Kim et al . investigated the remodeling pattern of the spinal canal after full‐endoscopic ULBD with a minimum follow‐up of 26 months and found that despite achieving sufficient decompression immediately 6 months postoperative, varying severities of asymptomatic restenosis were found in postoperative MRI without clinical significance 21 . Restenosis of the ULBD during follow‐up might remind surgeons to achieve sufficient decompression during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One MR radiological study by Kim et al . investigated the remodeling pattern of the spinal canal after full‐endoscopic ULBD with a minimum follow‐up of 26 months and found that despite achieving sufficient decompression immediately 6 months postoperative, varying severities of asymptomatic restenosis were found in postoperative MRI without clinical significance 21 . Restenosis of the ULBD during follow‐up might remind surgeons to achieve sufficient decompression during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…One MR radiological study by Kim et al investigated the remodeling pattern of the spinal canal after full-endoscopic ULBD with a minimum follow-up of 26 months and found that despite achieving sufficient decompression immediately 6 months postoperative, varying severities of asymptomatic restenosis were found in postoperative MRI without clinical significance. 21 Restenosis of the ULBD during follow-up might remind surgeons to achieve sufficient decompression during surgery. Several researchers have mentioned that the checkpoint of sufficient decompression obverts free and pulsatile neural elements, and adequate bony decompression of the cephalad/caudal lamina and ipsilateral/contralateral facet joint to expose the margin of the ligamentum flavum and resect the ligamentum flavum is important.…”
Section: Relationship Between Clinical Outcomes and Decompression Ran...mentioning
confidence: 99%